Pengaruh Keunggulan Bersaing Terhadap Loyalitas Pelanggan - Bendyi Afrianto; Ahmad Kamaludin (Papanda Publisher, 2023)
This study aims to determine the effect of competitive advantage on consumer loyalty. The research method used is descriptive and verification methods. The sample in this study were customers of Liang Julang